DISPARITIES VERDICT AGAINST THE CRIME OF THEFT BY SEVERE PUNISHMENT (Studies In State Court Liwa) - Sari, Emili (JURNAL POENALE, 2015)
Â AbstractCourt decisions on criminal cases of theft by weighting often poses legal difference is called the disparity in the judgment. The problem in this research is why the disparity in court decisions as well as whether the execution of court decisions already meet the substantive justice. Approach to the problem used in this thesis is a normative juridical approach and empirical jurisdiction. Results of research and discussion in mind that according to article 55 of the criminal code proved that Irawan bin Tohari are people who do their own crime (plegen) and the people who helped with a criminal offense (made plegen) seen from the chronology that bin Irawan Suganda Tohari are invited Imam bin Sudiyat do the crime of theft. While Imam Bin Sudiyat Suganda is the person who helped with a criminal offense only (made plegen) it can be seen that the act of Imam Suganda bin Sudiyat meet the requirement (made plegen). Implementation of court rulings have met the substantive sense of justice, because of sentences against people who have the intention of doing as well as jointly malakukan criminal offense hukumanya higher than that taken together committed the crime.Keywords : Disparity , court decisions , theft by weightingÂ